Medical benefits of Camel’s Milk: a comprehensive review - Sultan Fahad AlNohair (Journal of the Pakistan Medical Association, 2020)
Abstract In the last decade, there has been an emergent interest, supported by various experimental and epidemiological studies, for health benefits of camel milk, in preventing various pathologic conditions, ranging cancer to diabetes. However, the precise mechanisms by which camel milk induce these health benefits remain to be investigated. Various reports have shown that consumption of camel milk by diabetes patients on a daily basis reduces blood sugar and glycosylated hemoglobin (HbA1C) levels and also reduces insulin requirements. Despite that these findings provide scientific evidences of anti-diabetic activities of camel milk, research is yet to be initiated with assurance for patients of diabetes and other metabolic disorders. This review summarizes the medicinal values of bioactive constituents of camel milk and reviews camel milk findings from the most significant preclinical studies in diabetes. Keywords: Camel milk, diabetes mellitus, blood glucose, HbA1C, insulin resistance